Hit in the Heart of Life: How Meeting Like-Minded Peers May Contribute to Psychosocial Recovery of Adolescents and Young Adults With Acquired Brain Injury - Bakmann, Louise; Norup, Anne; Forchhammer, Birgitte Hysse (Frontiers in Neurology, 2019)
Adolescents and young adults are often in a particularly vulnerable position following acquired brain injury. In addition to neurological and cognitive impairment, they are faced with issues concerning education, job, family, and social life. Moreover, they may be limited in meeting peers and may be left alone with psychosocial issues. This paper investigates how this patient group may benefit from meeting like-minded peers. From information gathered through a questionnaire and interviews with participants in a peer support group, the study aimed to investigate the social and psychological advances such a group can offer, and how this may contribute to psychosocial recovery following acquired brain injury. Also, the paper indicates how peer support groups may possibly have an impact on the everyday lives of adolescents and young adults with acquired brain injury.